2009
DOI: 10.1162/neco.2009.08-08-837
|View full text |Cite
|
Sign up to set email alerts
|

Belief Propagation in Networks of Spiking Neurons

Abstract: From a theoretical point of view, statistical inference is an attractive model of brain operation. However, it is unclear how to implement these inferential processes in neuronal networks. We offer a solution to this problem by showing in detailed simulations how the belief propagation algorithm on a factor graph can be embedded in a network of spiking neurons. We use pools of spiking neurons as the function nodes of the factor graph. Each pool gathers "messages" in the form of population activities from its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…Several recent studies have considered how single neurons or their networks could implement belief propagation [52,55], or of how they could perform probabilistic computations in general [22,23,44,69]. Steimer et al [62] have shown how pools of spiking neurons can be used to implement the Belief-Propagation algorithm on a factor graph. The pools of neurons implement the nodes of a factor graph.…”
Section: Neuromorphic Cognitionmentioning
confidence: 99%
“…Several recent studies have considered how single neurons or their networks could implement belief propagation [52,55], or of how they could perform probabilistic computations in general [22,23,44,69]. Steimer et al [62] have shown how pools of spiking neurons can be used to implement the Belief-Propagation algorithm on a factor graph. The pools of neurons implement the nodes of a factor graph.…”
Section: Neuromorphic Cognitionmentioning
confidence: 99%
“…From this point of view, the parameter translation method raises the neural hardware and the computation they are able to achieve to a level of usability that until now was unaccessible by neuromorphic engineers. This ability can be expected to accelerate research on hardware emulation of interesting neuronal computational processes, such as hardware applications of liquid state machines (Maass, Natschläger, & Markram, 2002), and the implementation in spiking neurons of graphical models (Steimer, Maass, & Douglas, 2009). Rutishauser and Douglas (2009) have shown how state-machines can be composed of interconnected networks of winner-take-all (WTA).…”
Section: Discussionmentioning
confidence: 99%
“…5) If the graphical models are defined over singly-connected graphs (i.e. trees), then the marginals can be efficiently and exactly computed by belief propagation (BP) algorithms.…”
Section: §1 Introductionmentioning
confidence: 99%